Cement-Based Thermoelectric Materials, Devices and Applications - Li, Wanqiang; Du, Chunyu; Liang, Lirong; Chen, Guangming (Nano-Micro Letters, 2025)
Cement stands as a dominant contributor to global energy consumption and carbon emissions in the construction industry. With the upgrading of infrastructure and the improvement of building standards, traditional cement fails to reconcile ecological responsibility with advanced functional performance. By incorporating tailored fillers into cement matrices, the resulting composites achieve enhanced thermoelectric (TE) conversion capabilities. These materials can harness solar radiation from building envelopes and recover waste heat from indoor thermal gradients, facilitating bidirectional energy conversion. This review offers a comprehensive and timely overview of cement-based thermoelectric materials (CTEMs), integrating material design, device fabrication, and diverse applications into a holistic perspective. It summarizes recent advancements in TE performance enhancement, encompassing fillers optimization and matrices innovation. Additionally, the review consolidates fabrication strategies and performance evaluations of cement-based thermoelectric devices (CTEDs), providing detailed discussions on their roles in monitoring and protection, energy harvesting, and smart building. We also address sustainability, durability, and lifecycle considerations of CTEMs, which are essential for real-world deployment. Finally, we outline future research directions in materials design, device engineering, and scalable manufacturing to foster the practical application of CTEMs in sustainable and intelligent infrastructure. Highlights: 1 Covering the most cutting-edge advances in cement-based thermoelectric materials. 2 The first systematic summary of the preparation, performance and functional applications of cement-based thermoelectric devices. 3 The challenges and strategies for materials, devices and applications are fully discussed.